Optimising baffle layout for more balanced force distribution and progressive energy dissipation in high-velocity granular avalanches - Quanzhong Lu; Ning Hu; Bei Zhang; Zaiyan Wu; Da Huang; Hengxing Lan; Jianbing Peng (European Journal of Environmental and Civil Engineering, 2026)

Moderate introgression in a single individual genome is sufficient to mislead phylogenomic inference of Triplophysa - Zitu Ma; He Gao; Chuanshuai Xie; Da Ji; Yongrui Lu; Haoyu Wang; Yili Cui; Francisco de Menezes Cavalcante Sassi; Dengyue Yuan; Haiping Liu; Luohao Xu (Molecular Phylogenetics and Evolution, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

NIR-responsive mesoporous core-shell nanoplatform with oxygen self-supply and cascade targeting for reversing doxorubicin resistance via synergistic chemo-phototherapy - Yufeng Li; Yuping Jiang; Kexuan Wang; Xinyi Liu; Rui Yang; Lu Han; Tao He; Na Li; Da Huo (Chemical Engineering Journal, 2026)

Amphoteric-starch-functionalized palygorskite for calcium and magnesium ion regulation and paper-strength enhancement in wastepaper papermaking - Jianrong Da; Susu Yin; Ruixiang Xie; Yao Xu; Guanghui Lu; Huiyang Bian; Shumei Wang; Hongqi Dai; Tingting Xu (Applied Clay Science, 2026)

Quaternary climate-geography interactions triggered divergence in populations of the wax-myrtle shrub Morella adenophora on mainland southern China and the nearby islands of Hainan and Taiwan - Da-Xian Lu; Yu-Xia Lu; Jian Feng; Qin Yang; Chun-Xue Jiang; Tu Feng; Feng-Jiao Zhou; Cai Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Enhanced simultaneous nitrogen and phosphorus removal via a step-feed anoxic/oxic process coupled with side-stream enhanced biological phosphorus removal - Ruoyu Wu; Dongqi Wang; Mengbo Huang; Yanzhe Gong; Guangxiang Duan; Jiayu Bi; Wengui Gu; Lu Qin; Yuan Guo; Xiaopeng Qiu; Yishan Lin; Da Kang; et al. (Journal of Environmental Chemical Engineering, 2026)

Mainshock-aftershock fragility and risk analysis for RC frame structures based on Bayesian networks - Chang Liu; Da-Gang Lu (Engineering Structures, 2026)

Microbial mechanisms of sulfamethoxazole biodegradation at bio-anode elucidated by integrated metagenomics and stable-isotope probing - Hongli Lu; Hui Lin; Da Kang; Donglin Wang; Qiaojuan Wang; Jie Mao; Dan Cui; Yaohui Bai; Jiuhui Qu; Yongzhen Peng (Chemical Engineering Journal, 2026)

Plastic-mediated alterations in soil microbial networks and their role in sulfamethazine degradation - Yuqiu Ye; Luoqin Shen; Da Lin; Tianlun Zhang; Yaning Wang; Lu Lu; Yifei Qin; Dong Zhu (Journal of Environmental Sciences, 2026)

Evolution of PM2.5 chemical composition during summer new particle formation in a coastal city in the yangtze river delta: insights from pollution episodes, machine learning, and air mass origins - Han Zhou; Yichen Lu; Zeyi Li; Honglei Wang; Lijuan Shen; Yue Chen; Deyu Liu; Da Xu (Environmental Research, 2026)

Investigation of changes in microbial communities and metabolites for the nutrient re-utilization of fermented agricultural wastes in watermelon - Tong-Lu Wei; Yan-Ge Li; Mao-Song Pei; Hai-Nan Liu; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Biomass and Bioenergy, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Annexin A2 orchestrates CSFV entry route selection via the annexin A2/S100A10 heterotetrameric complex - Tao Wang; Liangcai Da; Junfang Zhao; Hong Yuan; Ying Sun; Liang Zhang; Jiaoyang Li; Kun Li; Jing Zhang; Pu Sun; Zhixun Zhao; Qiang Zhang; et al. (Veterinary Microbiology, 2026)

Application of a sulfonic acid-modified NE probe with low-toxicity in a mouse model of pneumonia - Fei Gao; Kai Wang; Jin-Lu Song; Dong-Nv Wang; Da-Ke Wen; Feng-Ming Liang; You-Zhen Feng; Zhong-Yuan Cheng (Journal of Photochemistry and Photobiology B: Biology, 2026)

An integrated assessment of provincial economic damages from climate change in China - Hantang Peng; Chen Fang; Tianpeng Wang; Yixiong Lu; Yang Qu; Junling Huang; Da Zhang; Xiliang Zhang; Xiaoye Zhang (Journal of Environmental Management, 2026)

A refined framework for assessing seismic direct economic losses of community building portfolios considering vulnerability uncertainty - Jia-Wei Ding; Da-Gang Lu; Zheng-Gang Cao (Engineering Structures, 2026)

Impact and rebound dynamics of mineral-heterogeneous rocks: From micromechanical mechanisms to energy-based modeling - Ning Hu; Sen Zhang; Bei Zhang; Quanzhong Lu; Hengxing Lan; Da Huang; Jianbing Peng (Computers and Geotechnics, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Research Progress on the Synthesis, Signal Transduction, and Functions of Plant Hormones in Potassium Deficiency Responses - Liu-Yang Wu; Shuai-Kun Wang; Hai-Nan Liu; Mao-Song Pei; Qiao-Fang Shi; Da-Long Guo; Tong-Lu Wei (Journal of Plant Growth Regulation, 2026)

Nitrogen removal performance of a submerged MABR-EGSB coupled reactor treating low C/N ratio wastewater - Liyuan Zhang; Bo Liu; Mingqi Dong; Zhe Qin; Chunxia Zhao; Da Lu (Journal of Water Process Engineering, 2026)

Investigation of the Fenton reaction of CIP@Fe3O4 and its polishing characteristics on single-crystal SiC - Da Hu; Jiabin Lu; Liyun Su; Huaian Yi; Enchi Xue (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into hexamethylphosphoramide degradation and phosphorus recovery via mZVI/O3: Beyond conventional oxidation through iron-phosphorus speciation - Da Wang; Wenqian Hu; Yumeng Zheng; Zihan Xia; Haijun Cheng; Xiaohui Lu; Zhiqiao He; Stefanos Giannakis; Shuang Song; Jun Ma (Chemical Engineering Journal, 2026)

Multidimensional dissection of shared genetic susceptibility in ulcerative colitis and colorectal cancer: novel insights from integrative single-cell and multi-omics analysis - Fanfan Zhu; Xin Yao; Da Liu; Shanshan Wang; Xuyu Huang; Jing Zhou; Song Wang; Shanneng Tang; Dongping Lai; Shuang Yang; Xiaobing Meng; Xinyue Zhang; et al. (Inflammation Research, 2026)

The VvSAP8-VvHAK5 module from grape confers dual tolerance to potassium deficiency and salt stress by regulating potassium transport - Tong-Lu Wei; Ze-Hang Wang; Liu-Yang Wu; Shuai-Kun Wang; Qiao-Fang Shi; Mao-Song Pei; Hai-Nan Liu; Da-Long Guo (Plant Cell Reports, 2026)

A CNN-LSTM-Attention model for risk prediction of offshore wind turbines - Jia-Xuan Li; Da-Gang Lu; Jia-Wei Ding; Yong Ding; Hao Liu; Libo Chen; Wenbing Wu (Ocean Engineering, 2026)

A Bayesian network approach to multi-hazard risk assessment of offshore wind turbines - Jia-Xuan Li; Da-Gang Lu; Hao Liu; Wenbing Wu (Ocean Engineering, 2026)

Polishing performance of single-crystal SiC with a magnetically controll-fenton reaction magnetorheological elastomer pad - Da Hu; Kexin Liu; Enchi Xue; Liangji Chen; Jiabin Lu (Journal of Environmental Chemical Engineering, 2026)

Predatory performances and adaptive strategies of Eocanthecona furcellata (Hemiptera: Pentatomidae) to the larvae of Phauda flammans (Lepidoptera: Phaudidae) - Jian-Zhong Ning; Da-Xing Lu; Xiong Zhao He; Xiao-Yun Wang; Kai Lin; Jun Li; Xia-Lin Zheng (Applied Animal Behaviour Science, 2026)

In situ amidation of NH3 in biogas on sludge-derived carbon to promote coexisting CO2 adsorption - Zhangliang Han; Aoran Zhang; Shuofei Yuan; Xinyue Lu; Shuangxi Fang; Juntao Tang; Da Wang; Zhiqiao He; Feilong Dong; Shuang Song (Water Research, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Boron and oxygen isotopes fractionation between borate minerals and fluids and implications for borate deposit formation - Da-Sheng Zuo; Hai-Zhen Wei; Jian-Jun Lu; M.R. Palmer; A.E. Williams-Jones; Jun-Lin Wang; Shao-Yong Jiang; Ke Yang; He-Feng Lin; Simon V. Hohl; Yi-Chu Chen (Applied Geochemistry, 2026)

Impact of PM2.5 exposure on gut microbiota abundance and composition in chronic disease patients - Yi-Hsueh Liu; Po Peng; Wei-Chun Hung; Ping-Hsun Wu; Chun-Chi Lu; Yi-Hsiung Lin; Chih-Da Wu; Chao-Hung Kuo; Szu-Chia Chen (Air Quality, Atmosphere & Health, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

Efficacy of copper alloy coatings in controlling Ichthyophthirius multifiliis infections: a sustainable alternative for freshwater aquaculture - Zi-Hong Guo; Wen-Hao Wu; Ming-Da Chen; Zi-Jian Long; Jian-Cheng He; Jia-Hao Zhang; You-Lu Su; Biao Jiang (Aquaculture, 2026)

Evaluation of residual virulence and protective efficacy for Brucella melitensis vaccine strain M5-90 in mice and guinea pigs - Chenchen Lu; Chenglan Zhang; Yanan Li; Zujian Qiao; Xijun Wang; Weiye Chen; Xiaoyi Chen; Qian Jiang; Da Xu; Zhigao Bu; Sen Hu (Veterinary Microbiology, 2026)

ANXA2 stabilizes mTOR at the plasma membrane to facilitate autophagic flux for CSFV release - Tao Wang; Liangcai Da; Junfang Zhao; Hong Yuan; Ying Sun; Liang Zhang; Kun Li; Jing Zhang; Pu Sun; Zhixun Zhao; Qiang Zhang; Yuanji Zhang; et al. (Veterinary Microbiology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The first cranium of Postschizotherium (Pliohyracidae, Hyracoidea) from the Lower Pleistocene of China - Lu-Da Xing; Xiao-Bing Wang; Martin Pickford; Yan-Jie Chen; Jiao Ma; Shu-Qiong Wang; Yi-Yang Liu; Shi-Qi Wang (Palaeoworld, 2026)

Regional and temporal differences in residential occupancy patterns: A TUS-based analysis - Yuxin Lu; Xin Zhou; Shan Hu; Mingyang Qian; Da Yan (Energy and Buildings, 2026)

Crustal growth and modification of the Muzidian Gneiss complex revealed by detrital zircon from modern river sediments - Xiao-Fei Qiu; Xi-Run Tong; Da Wang; Xin Deng; Shan-Song Lu (Chemical Geology, 2026)

Three new flavonoid glycosides from the herbaceous stems of Ephedra intermedia - Ying Niu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Di Lu; Xiao-Ke Zheng; Wei-Sheng Feng (Natural Product Research, 2026)

Fully automated [18F]AlF radiolabeling using a microdroplet reactor platform - Yingqing Lu; Gitanjali Sharma; Chiara Da Pieve; Gabriela Kramer-Merek; Philip W. Miller; R. Michael van Dam (Chemical Engineering Journal, 2026)

Comprehensive insights into the thermal decomposition behavior, mechanism, and mineralization of PFOS, PFOSA, F 53B, PFOA, and 8:2 FTOH and toxicity prediction of their gaseous products - Yun Deng; Jiankun Huang; Xingwen Lu; Da Chen; Fei Wang (Chemical Engineering Journal, 2026)

Spatial phylogenetics and biocultural conservation of medicinal plants in ethnic minority communities of china: implications for environmental sustainability - Da-Cheng Hao; Yaoxuan Wang; Zhi-Duan Chen; Li-Min Lu; Pei-Gen Xiao (Biodiversity and Conservation, 2026)

Nicotinamide delays browning in fresh-cut apples through reducing Chlorogenic acid and inhibiting PPO activity - Chen Wang; Lu-Ping Dai; Xin-Ran Bai; Song Zhang; Pei-Qiang Dai; Bao-Long Zhao; Feng-Yun Zhao; Da-Gang Hu (Food Chemistry, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Glued laminated bamboo roof trusses with stainless-steel tubular rivet connections: Connection and global behavior - Guoshan Lu; Hanlin Wei; Da Shi; Zhi Li; Beibei Xiong; Tommaso Albanesi; Carlotta Contiguglia; Cristoforo Demartino (Engineering Structures, 2025)

Neutrophil extracellular trap (NET)-targeted nanoparticles alleviate myocardial ischemia–reperfusion injury in mice by inhibiting macrophage–myofibroblast transition - Da Lu; Wei Jiang; Xi Zhang; Jiangshui Liang; Meng Xiong; Changzhi Yan; Anyi Lin; Teng Ma; Feng Zhu; Yongqiang Dong (Chemical Engineering Journal, 2025)

Enhanced piezoelectric demulsification for high-efficiency separation of water-in-oil (W/O) emulsions based on biomimetic PVDF/liquid metal nanofiber membranes - Wen-Qiang Qiu; Jia-Qi Luo; Qing-Ke Luo; Yan-Ping Zhao; Zhi-Yu Xue; Jing-Song Tang; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Combustion Behavior and Thermal Disaster Quantification of Weathered Water-Saturated Coal in an Oxygen-Poor Environment of Goaf - Hui-yong Niu; Hao-liang Zhu; Qing-qing Sun; Hai-yan Wang; Gong-da Wang; Lu-lu Sun (Natural Resources Research, 2025)

Identification of grape H3K27 methyltransferase genes and their expression profiles during grape fruit ripening - Ding-Ding Zuo; Hao-Ting Sun; Lu Yang; Fang-Hui-Zi Shang; Da-Long Guo (Molecular Biology Reports, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Corrigendum to “Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs” [Vet. Microbiol. 305 (2025) 110529] - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Da Liu; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Risk assessment of spatially distributed assets with generalized seismic fragility models based on machine learning - Jia-Wei Ding; Da-Gang Lu; Zheng-Gang Cao (Soil Dynamics and Earthquake Engineering, 2025)

Ru8@NU-1000 as difunctional photocatalysts for visible-light-driven efficient CO2 reduction integrated with furfurylamine oxidation - Jiayi Zhang; Yanan Qu; Kang Bu; Jingting Lu; Da Chen; Huafeng Li; Liqun Bai (Fuel, 2025)

Bench- and pilot-scale degradation of organic pollutants in high-salt wastewater using air microbubble discharge plasma jet - Jian-Ping Liang; Da-Wei Ge; Ke Lu; Hao Yuan; Chao-Jun Chen; Zi-Kai Zhou; De-Zheng Yang (Desalination, 2025)

Hydrogen production from supercritical water gasification of corn stalk with reactive co-solvents: Regulator roles of free radicals - Da Cui; Xuelong Sui; Yuqi Wang; Hon Man Luk; Shuang Wu; Chunlei Wu; Jinghui Zhang; Qiuyun Lu; Qing Wang; Xuehua Zhang (Chemical Engineering Journal, 2025)

ULK1-dependent phosphorylation of OGT instructs the tumorigenicity of O-GlcNAcylation - Zhuan Lv; Qingen Da; Yumiao Li; Aiyun Yuan; Guangcan Shao; Xiaoxuan Lu; Yue Wang; Xuefang Zhang; Jingjing Liu; Meng-Qiu Dong; Yuanyuan Ruan; Chen Wu; et al. (Science China Life Sciences, 2025)

Selection of optimal seismic intensity measures for evaluating liquefaction triggering: accounting for the influence of liquefiable sites - Jian-Yu Meng; Bao-Hua Shan; Da-Gang Lu (Natural Hazards, 2025)

Humic substances initiated superior photochemical pollutant conversion in environmentally relevant matrices: When ZnO met MoS2 as electron mediator - Jia-Sheng Li; Song Hu; Ling-Feng Wang; Wei Da; Ai-Yong Zhang; Lu Zhao; Jing-Yu Zhang (Journal of Environmental Chemical Engineering, 2025)

Eco-friendly eugenol curing agent-derived biobased epoxy resins for multi-functional integration - Zhiyong Li; Xiangyan Ji; Xiaoge Li; Da Gao; Lei Shen; Wei He; Jie Sun; Dingqiang Lu; Jingjing Meng; Kai Guo (Chemical Engineering Journal, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Speciation Caught in the Act: Derived Ciliary Patterns Budded Off From the Oxytricha granulifera ‐Like Lineages (Alveolata, Ciliophora) - Linger Lu; Tian Wang; Lingzhi Ye; Zhangwen Tong; Zina Lin; Xiaotian Luo; Thiago da Silva Paiva; Xinpeng Fan (Zoologica Scripta, 2025)
Oxytricha is a well‐known ciliate genus having a long, but convoluted taxonomic history, which aside from its non‐monophyly and subsequent dismembering into other genera, has a major issue: the type species O. granulifera is consistently paraphyletic. To understand their paraphyly in the context of our perception of species and genera according to the integrated taxonomy concept, we evaluated the phylogenetic status of different O. granulifera ‐like populations using nuclear and mitochondrial genes. We demonstrate that in the clade formed by O. granulifera and its closely related species, which we designate as the ‘OAN‐clade’, O. granulifera populations have diverged into distinct sub‐clades; and these sub‐clades also encompass O. atypica , Architricha indica and Neogastrostyla species including the herein described N. chongmingensis nov. spec. Genetic variations discerned through the secondary structure of ITS2 molecules, pairwise genetic distances of the COI gene, and a range of phylogenetic trees indicate that speciation events have widely occurred within the OAN‐clade, with Architricha , Neogastrostyla and O. atypica evolving from certain O. granulifera ‐like lineages by developmental changes and other lineages retaining ancestral characteristics of O. granulifera . Moreover, our results reveal a recognisable pattern of environmental transition between freshwater and soil in the OAN‐clade, which provides a clue for further splitting the O. granulifera ‐ like populations. Additionally, our findings suggest that cortical granules, as is the case of cyathiform mucocysts containing glycosylated proteins present in the OAN‐clade, could serve as a criterion for delimiting the genus Oxytricha and the family Oxytrichidae, thus excluding other Oxytricha species with other kinds of cortical granules or lacking them.

Improving the data quality of CO2 continuous emissions monitoring systems: In the context of China's emissions trading scheme - Yi Song; Xiaohu Luo; Yuhao Lu; Jueying Qian; Wei Zhang; Liangke Liu; Junling Huang; Xiaolu Zhao; Da Zhang (Environmental Impact Assessment Review, 2025)

Inferring absolute cell numbers from relative proportion in stochastic models with cell plasticity - Yuman Wang; Shuli Chen; Zhaolian Lu; Yu Liu; Jie Hu; Da Zhou (Journal of Theoretical Biology, 2025)

Binders with cationic semi-interpenetrating networks for sodium-ion batteries under extreme conditions - Chen-Hui Yang; Chi-Hon Leung; Lan-Fang Que; Fu-Da Yu; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Mechanism of pH-sensitive Amphiphilic Endosomal Escape of Ionizable Lipid Nanoparticles for Cytosolic Nucleic Acid Delivery - Zheng-Rong Lu; Da Sun (Pharmaceutical Research, 2025)
Lipid nanoparticles (LNPs) are among the most successful classes of nonviral delivery systems for nucleic acid-based therapeutics in treating human diseases. One of the key challenges in achieving efficient cytosolic delivery of nucleic acids is overcoming endosomal entrapment within cells. Conventional lipid bilayer-forming cationic and amino lipids mediate endosomal escape via the mechanism of lamellar-to-inverted hexagonal phase transition, resulting in suboptimal cytosolic cargo delivery. pH-sensitive amphiphilic cell membrane disruption and endosomal escape have emerged as a strategy for designing protonatable or ionizable lipids, especially nonlamellar lipids, for efficient cytosolic nucleic acid delivery. Nonlamellar amino lipids possess a large wedge-shaped tail structure and do not form stable lipid bilayers. These lipids and their corresponding LNPs remain neutral, non-amphiphilic, or minimally amphiphilic at physiological pH (7.4). They become amphiphilic upon protonation or ionization in acidic endosomes (pH 6.5–5.4). The electrostatic interaction of ionized nonlamellar lipids with the negatively charged endosome membrane, combined with their large wedge-like structures, disrupts the lipid bilayer, facilitating efficient endosomal escape. Additionally, the nonlamellar ionizable lipids can be fine-tuned by altering the structure of amino head groups and lipid tails to achieve the precisely controlled pH-sensitive amphiphilic membrane disruption at endosomal pH. Therefore, these lipids exhibit excellent safety profiles and high efficiency for in vivo delivery of various therapeutic nucleic acids. pH-sensitive amphiphilic membrane disruption and endosomal escape provide a feasible and effective mechanism for designing ionizable lipids for safe and efficient in vivo nucleic acid delivery.

The Role of Hydrogen Peroxide in Fruit Ripening Regulation - Lu Yang; Ding-Ding Zuo; Da-Long Guo (Journal of Plant Growth Regulation, 2025)

Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Liu Da; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Targeting DUSP3 promotes cell senescence by activating the notch1 pathway to treat hepatocellular carcinoma - Wen-Jun Zhang; Jun-Lu Peng; Da-Fei Dai; Chen Huang; Xiao-Peng Chen (Tissue and Cell, 2025)

Nanoparticle contrast agent Mn3O4/SiO2/C as an ozonation catalyst with unexpected synergy in degrading organic contrast agent iopamidol: an effective “treat-waste-with-waste” strategy for medical wastewater - Wen Xu; Shiwen Dong; Haijun Cheng; Stefanos Giannakis; Xiaohui Lu; Zhiqiao He; Da Wang; Shuang Song; Jun Ma (Chemical Engineering Journal, 2025)

Land-use types impact soil ecosystem functions by altering the soil multitrophic biodiversity and interactions - Tian-Lun Zhang; Shao-Yang Zhang; Lu Wang; Da Lin; Bang Ni; Tian-Gui Cai; Shuai Du; Dong Zhu (Soil Ecology Letters, 2025)

Three-Dimensional Shallow P-wave Velocity Distribution in the Source Area of the 2021 MS6.0 Luxian Earthquake from Dense Array Seismic Imaging - Jian-xun Yang; Qi-yan Yang; Da-hu Li; Yong-ming Lu; Ping-ping Wu; Hui-li Guo; Ning-bo Jiang; Mi Gao; Heng Pan (Applied Geophysics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Enhanced treatment efficiency of moxifloxacin-containing domestic wastewater in sequence batch reactors coupled with Spartina alterniflora biochar - Yuan-da Du; Yanan Gao; Mengyu Qin; Jian Liu; Shoubo Zhao; Haolin Mu; Xinru Lu; Shun Zheng; Xiaojing Chen; Zishu Wu; Qiang Kong; Jian Zhang (Journal of Water Process Engineering, 2025)

Far-red light-driven photoautotrophy of chlorophyll f-producing cyanobacterium without red-shifted phycobilisome core complex - Da Huang; Tong Wei; Min Chen; Shu-Jun Chen; Jia-Yue Wu; Lu-Dan Zhang; Hai-Feng Xu; Guo-Zheng Dai; Zhong-Chun Zhang; Bao-Sheng Qiu (Photosynthesis Research, 2025)

Beyond traditional uses: the multifaceted bioactivities of steroidal saponins from the genus Trillium and their modern applications - Dong-Sheng Fan; Lu Yu; Xiao-Gang Zhou; Yue Zhang; Dong Yi; Qi-Bing Mei; Da-Lian Qin; Jian-Ming Wu; An-Guo Wu (Phytochemistry Reviews, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Comparative efficacy of anaerobic digestion systems in removing antimicrobial resistance genes from swine wastewater - Da Sun; Xiaomin Shi; Yingbo Shen; Ying Liu; Sunlin Luo; Yongpeng Jin; Weishuai Zhai; Lu Liu; Zhaoju Deng; Chengtao Sun; Dejun Liu; Xin Yang; et al. (Journal of Hazardous Materials, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Accelerated stochastic processes of plankton community assembly due to tidal restriction by seawall construction in the Yangtze River Estuary - Xingyu Chen; Ailing Yan; Shiqiang Lu; Haoran Zhang; Da Li; Xiaodong Jiang (Marine Environmental Research, 2025)

Dual role of multistage inoculation in manipulating bacterial community assembly patterns to improve degradation of lignocellulose during rice or corn straw composting - Da Liu; Ziwei Jiang; Wenxuan Feng; Yufeng Zhao; Pengfei Tang; Jizhe Cui; Zhan Zhao; Qian Lu (Chemical Engineering Journal, 2025)

Steady-state analysis of Xi’an Pulse Reactor based on the multi-physics coupling method - Tianliang Hu; Duoyu Jiang; Xinyi Zhang; Zhaohao Wang; Lipeng Wang; Lu Cao; Da Li; Lixin Chen (Annals of Nuclear Energy, 2025)

Strategic analysis of avian conservation within key areas and key species – A case study of Baiyangdian, China - Zengrui Tian; Zhenguang Lu; Da Huo; Zongjun Zhang; Qi Sun; Heng Wu; Jiaojiao Wang; Yitong Kang; Yu Xie; Yongchang Tian; Kunpeng Yi; Jianhua Hou (Journal of Environmental Management, 2025)

Bond-slip behavior of Aluminum Alloy (AA) bars for near-surface mounted (NSM) technique - Xu Chen; Guohua Xing; Da Luo; Yongjian Lu; Zhaoqun Chang; Enrique del Rey Castillo; Jason Ingham (Engineering Structures, 2025)

High-Performance wave loss capability by Constructing Well-Defined hierarchical aerogel framework with strongly coupled Carbon/CeO2 interface - Yun-Xia Bai; Da-Peng Liu; Lu Zhou; Bo Cai; Pei-Yan Zhao; Hua-Long Peng; Yu Zhang; Qi-Fan Xuan; Wen-Hao Liang; Zhi-Ling Hou; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

Development of chromosome-specific potential intron polymorphism markers in watermelon - Liang-Jie Li; Ding-Ding Zuo; Meng-Ling Zheng; Lu Yang; Rui Sun; Xue‑Jie Zhu; Zhong‑Hou Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Ultrasound-Targeted β-Catenin Gene Therapy Improves the Cardiac Function in Mice After Myocardial Infarction - Lei Yang; Tong Gao; Yu Huang; Pei-he Wang; Xin-hao Han; Jie Wu; Lei Huang; Qing-en Da; Kun-fu Ouyang; Zhen Han; Hai Tian; Lu Sun (Cardiovascular Toxicology, 2025)

Constraints of upper crust magmatic processes on the formation of Saindak porphyry Cu deposit: Insights from mineral geochemistry - Lu Wang; Zi-xuan Wang; Yuan-chuan Zheng; Zeng-qian Hou; Zhu-sen Yang; Chang-da Wu; Xin Li (Lithos, 2024)

Accelerating peroxymonosulfate activation over fiber-shaped Fe@Fe3C/CNF for ultrafast tetracyclines degradation: Active site synergy and mechanisms - Man Yang; Yafan Lu; Wenjuan Zhang; Long Xie; Junjie Tian; Yiliyasi Baikeli; Fang Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Mika Sillanpää; Longlong Geng (Journal of Environmental Chemical Engineering, 2024)

High sensitive Ratiometric fluorescent Aptasensor with AIE properties for Deoxynivalenol (DON) detection - Yuandong Lin; Nian Lu; Ji Ma; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2024)

Insights into the accumulation and hepatobiliary transport of bisphenols (BPs) in liver and bile - Jie Ding; Ying Liu; Yanjie Li; Yongheng Huang; Shibo Li; Fei Wang; Da Chen; Bin Lu; Nan Lin (Environmental Research, 2024)

Hydrogen peroxide priming triggers splicing memory in grape berries - Ding-Ding Zuo; Hao-Ting Sun; Lu Yang; Meng-Ling Zheng; Jing Zhang; Da-Long Guo (Plant Molecular Biology, 2024)

Adventitious shoot organogenesis from immature leaves of sugarcane (Saccharum spp. hybrid) cultivar Yuetang 03-373 improving shoot proliferation and industrial scale-up of plants - Shuangyan Chen; Yinglin Lu; Qingwen Luo; Jiana Tan; Jinyan Guan; Jianpiao Luo; Yuchan Xu; Mengyi Chen; Rui Zhao; Jaime A. Teixeira da Silva; Yifei Zhang; Guohua Ma (Journal of Crop Science and Biotechnology, 2024)

Towards sustainable fruit production: Identifying challenges and optimization strategies - Liangquan Wu; Xiaojun Yan; Jiayi Huang; Xiuzhu Xu; Siwen Zhang; Shilei Cui; Xiaohui Chen; Zhixiong Zeng; Shuangyong Huang; Yingzhe Zeng; Yibin Weng; Bingkun Lu; et al. (Agricultural Systems, 2024)

Comparative analysis of size-fractional eukaryotic microbes in subtropical riverine systems inferred from 18S rRNA gene V4 and V9 regions - Guanglong Zhang; Zhenli Guo; Yue Ke; Hanyi Li; Xilin Xiao; Da Lin; Lujian Lin; Yanhong Wang; Jingchun Liu; Haoliang Lu; Hualong Hong; Chongling Yan (Science of The Total Environment, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

A fluorescent Aptasensor based on magnetic-separation strategy with gold nanoclusters for Deoxynivalenol (DON) detection - Nian Lu; Ji Ma; Yuandong Lin; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2024)

Novel insights and future perspectives on the nanomedicine-mediated synergistic anticancer effect of the combination of ferroptosis and photothermal therapy - Hengkai Qi; Haiying Wang; Lu Wang; Da Sun; Minjie Wei; Zhenhua Li (Chemical Engineering Journal, 2024)

Feasibility of an environmental scan–based approach to collecting information about factors impacting cancer genetics services in Latin American countries - Erica M. Bednar; Roni Nitecki Wilke; Kirsten Jorgensen; Michael T. Walsh; Stephanie Nutt; Karen H. Lu; Leandro Nóbrega; Aline Patricia Soares Dias De Souza; Gabriela da Silva Oliveira; Carlos Eduardo Mattos da Cunha Andrade; Nelson Purizaca-Rosillo; Pamela Mora; et al. (Journal of Community Genetics, 2024)

On CO2 efficiency and trade-offs between sustainability, safety, economy and resilience in infrastructure developments - Min Liu; Da-Gang Lu; Michael Havbro Faber (Sustainable Cities and Society, 2024)

Particle-ozone complex pollution under diverse synoptic weather patterns in the Yangtze River Delta region: Synergistic relationships and the effects of meteorology and chemical compositions - Yangzhihao Zhan; Min Xie; Bingliang Zhuang; Da Gao; Kuanguang Zhu; Hua Lu; Tijian Wang; Shu Li; Mengmeng Li; Yi Luo; Runqi Zhao (Science of The Total Environment, 2024)

Analysis of stage parameters of low-temperature oxidation of water-soaked coal based on kinetic principles - Yun-chuan Bu; Hui-yong Niu; Gong-da Wang; Tian Qiu; Yan-xiao Yang; Lu-lu Sun (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A new type of dolomicrite envelope formed in Oligocene lacustrine sediments and its significance for preserving porosity, Bohai Bay Basin, North China - Caineng Mu; Xiaobo Huang; Liya Da; Anqing Chen; James G. Ogg; Huan Lu; Yuzhu Ge; Jian Luo; Siyu Xiong; Haiyang Cao; Mingcai Hou (Sedimentary Geology, 2024)

Two undescribed monoterpenoids from the fruit of Gardenia jasminoides Ellis - Di Lu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Ying Niu; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Sea surface carbon dioxide during early summer at the Tuandao nearshore time series site - Lu Cao; Yongqi Qiu; Liang Xue; Yingying Zhang; Shuwei Zhang; Ning Wu; Da Yuan; Quanlong Li; Zheng Zhao; Ning Wang; Yan Zhou; Wei Yang; et al. (Marine Environmental Research, 2024)

Species-level understanding of the bacterial community in Daqu based on full-length 16S rRNA gene sequences - Pei-Jie Han; Liang Song; Zhang Wen; Hai-Yan Zhu; Yu-Hua Wei; Jian-Wei Wang; Mei Bai; Lu-Jun Luo; Ju-Wei Wang; Shen-Xi Chen; Xiao-Long You; Da-Yong Han; et al. (Food Microbiology, 2024)

Multi-process atmospheric particle number size distribution over the Bohai Sea: Insights from cruise and onboard unmanned aerial vehicle observations - Ziwei Liu; Hao Li; Jie Tang; Mian Wang; Haitao Zheng; Tao Luo; Xiaoquan Song; Chengfeng Liu; Guochen Wang; Xiaofei Qin; Jia Chen; Da Lu; et al. (Atmospheric Environment, 2024)

Low-dose 60Co-γ-ray irradiation promotes the growth of cucumber seedlings by inducing CsSAUR37 expression - Shengnan Li; Ke Lu; La Zhang; Lianxue Fan; Wei lv; Da jun Liu; Guojun Feng (Plant Molecular Biology, 2024)

Novel Sustained Release Azithromycin Resinate Fabricated by One-Pot Ion-exchange Performed in Hydro-alcoholic Solution - Hongyu Liang; Meihui Zhao; Shaoning Wang; Da Wang; Jingxin Gou; Yanjie Bai; Mingyue Shen; Junfeng Wang; Yujie Cheng; Ning Ge; Yi Zhao; Jie Zeng; et al. (AAPS PharmSciTech, 2024)

Regulating iron center by defective MoS2 for superior Fenton-like catalysis in water purification: The key role of surface interaction and superoxide radical in accelerating metal redox-cycling - Ai-Yong Zhang; Zhi-Xian Lin; Jing-Yu Zhang; Ming-He Zhang; Chi Zhang; Lu Zhao; Liang Liu; Wei Da; Lyumeng Ye (Chemosphere, 2024)

Refining metallic nano-copper by electron-rich black carbon for superior Fenton-like catalysis in water purification: The capacitive regulation of corrosive electron transfer - Lu Zhao; Xing-Bo Chen; Xin-Ru Hu; Lei Chen; Shun Feng; Ai-Yong Zhang; Shu-Chuan Peng; Zhi-Xian Lin; Chu Jiang; Wei Da; Qi-Xin Wei (Journal of Hazardous Materials, 2024)

Shallow-water redox evolution from the Ediacaran to the early Cambrian: Linkages to the early animal innovations - Guang-Yi Wei; Da Li; Zunli Lu; Ganqing Jiang; Hong-Fei Ling (Global and Planetary Change, 2024)

Understanding the structural relation and electrochemical evolution between ZnGeP2 and ZnSiP2 twin phosphides for advanced Li-ion batteries - Wei Liang; Bin Chen; Da Li; Xuhao Liu; De Li; Xuan Tian; Panpan Zhang; Xing Lu; Yaqing Wei; Yong Chen (Chemical Engineering Journal, 2024)

BDM: An Assessment Metric for Protein Complex Structure Models Based on Distance Difference Matrix - Jiaqi Zhai; Wenda Wang; Ranxi Zhao; Daiwen Sun; Da Lu; Xinqi Gong (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Status and trends in the stability of the three largest ice shelves in Antarctica - Rongxing Li; Guojun Li; Lu An; Menglian Xia; Da Lv; Yuan Cheng; Aiguo Zhao; Tian Chang; Xiangbin Cui; Shengkai Zhang; Shijie Liu; Yixiang Tian; et al. (Science China Earth Sciences, 2024)

Assessment of co-benefits from on-road vehicle electrification in Suzhou City, China - Feiyue Qian; Cui Da; Chunchen Lu; Xinyu Gu; Junjian Yang; Chaowei Shi; Zhen Feng; Yuanyuan Cheng (Urban Climate, 2024)

Numerical study on the coupling effect of river attributes and riverside building forms on the urban microclimate: A case study in Nanjing, China - Yuxie Zhou; Yuxin Lu; Xin Zhou; Jingjing An; Da Yan (Sustainable Cities and Society, 2024)

Newly graphene/polypyrrole (rGO/PPy) modified carbon felt as bio-cathode in bio-electrochemical systems (BESs) achieving complete denitrification - Yue-Jia Yang; Shuai Wang; Da Kang; Xin Lu; Zi-Chang Lu; Zhuo-Chao Liu; Li-Ming Yang; Dan Cui (Environmental Research, 2024)

Correction: Structure and Function of Cationic and Ionizable Lipids for Nucleic Acid Delivery - Da Sun; Zheng-Rong Lu (Pharmaceutical Research, 2024)

A measure for seismic multiple bends and shear damage patterns of RC rigid-frame bridge tall piers - Zhu Mei; Yang Liu; Bin Wu; Oreste S. Bursi; Da-gang Lu; Fabrizio Paolacci (Bulletin of Earthquake Engineering, 2024)

Association between outdoor air pollutants and risk of acute exacerbation of chronic obstructive pulmonary disease in Xi’an, China - Xinping Fan; Xueyan Jie; Fan Zou; Dan Wang; Hongju Da; Hongxin Li; Hongyan Zhao; Jin He; Jianghao Liu; Yiyi Lu; Yun Liu (Air Quality, Atmosphere & Health, 2024)

One-step rapid achieving O-SWCNHs@SiO2 core–shell heterostructures with tunable electromagnetic absorption performance via arc plasma - Zhipeng Xie; Yichang Liu; Shuiqing Lu; Jiale Chen; Haiyang Peng; Bin Yang; Da Zhang; Jianjun Wu; Feng Liang (Chemical Engineering Journal, 2024)

Transient multi-physics coupling analysis of the Xi'an Pulsed Reactor under pulsed condition - Duoyu Jiang; Peng Xu; Tianliang Hu; Xinbiao Jiang; Da Li; Xiaoyan Tian; Lipeng Wang; Yongping Wang; Xinyi Zhang; Lu Cao (Annals of Nuclear Energy, 2024)

Micro-structure change and crystal-structure modulated of oxygen carriers for chemical looping: Controlling local chemical environment of lattice oxygen - Da Song; Tao Long; Cuiqin Li; Yang Li; Mingyang Fan; Yonghao Lu; Yuchao Zhou; Haitao Chen; Yan Lin; Zhen Huang; Fang He (Fuel, 2024)

Humic substances mediated superior photochemical pollutant conversion on defective TiO2 in environmentally relevant matrices: The key roles of oxygen vacancy in surface interactions, oxidant activation and radical generation - Song Hu; Lyumeng Ye; Bing-Jie Tian; Jia-Ying Li; Ai-Yong Zhang; Lu Zhao; Chi Zhang; Chu Jiang; Zhi-Xian Lin; Wei Da; Qi-Xin Wei (Science of The Total Environment, 2024)

Optimizing utilization strategy of real-time SHM information for structural integrity management based on preposterior decision analysis - Wei-Heng Zhang; Jianjun Qin; Da-Gang Lu; Min Liu; Michael Havbro Faber (Ocean Engineering, 2024)

Effect of liver cancer on the accumulation and hepatobiliary transport of per- and polyfluoroalkyl substances - Ying Liu; Lin Peng; Yanjie Li; Xingwen Lu; Fei Wang; Da Chen; Nan Lin (Journal of Hazardous Materials, 2024)

Intravitreal Delivery of PEGylated-ECO Plasmid DNA Nanoparticles for Gene Therapy of Stargardt Disease - Da Sun; Wenyu Sun; Song-Qi Gao; Jonathan Lehrer; Hong Wang; Ryan Hall; Zheng-Rong Lu (Pharmaceutical Research, 2024)

Development of risk-targeted hazard maps with second-order hazard approximation for mainland China - Cong Wang; Da-Gang Lu; Ser Tong Quek (Soil Dynamics and Earthquake Engineering, 2024)

Natural attenuation of BTEX and chlorobenzenes in a formerly contaminated pesticide site in China: Examining kinetics, mechanisms, and isotopes analysis - Mengjie Wang; Dengdeng Jiang; Lu Yang; Jing Wei; Lingya Kong; Wenyi Xie; Da Ding; Tingting Fan; Shaopo Deng (Science of The Total Environment, 2024)

Inhibition of quorum sensing serves as an effective strategy to mitigate the risks of human bacterial pathogens in soil - Jinghan Zhang; Kun Lu; Lin Zhu; Na Li; Da Lin; Yangjuan Cheng; Meizhen Wang (Journal of Hazardous Materials, 2024)

Pre-stack Seismic Probabilistic Inversion Method for Lithofacies and Elastic Parameters of Volcanic Reservoir - Da Zhang; Cai Liu; Pengfei Zhao; Qi Lu; Yinghan Qi (Pure and Applied Geophysics, 2024)

Investigation analysis of the acute asthma risk factor and phenotype based on relational analysis with outdoor air pollutants in Xi’an, China - Yiyi Lu; Xueyan Jie; Fan Zou; Dan Wang; Hongju Da; Hongxin Li; Hongyan Zhao; Jin He; Jianghao Liu; Xinping Fan; Yun Liu (Environmental Geochemistry and Health, 2024)

Role of probiotics/synbiotic supplementation in glycemic control: A critical umbrella review of meta-analyses of randomized controlled trials - Dengfeng Xu; Lingmeng Fu; Da Pan; YiFang Chu; Meiyuan Feng; Yifei Lu; Chao Yang; Yuanyuan Wang; Jiayue Xia; Guiju Sun (Critical Reviews in Food Science and Nutrition, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Simultaneously tuning oxygen reduction pathway and charge transfer dynamics toward sacrificial agent-free photocatalytic H2O2 production for in-situ water disinfection - Ya-Ya Yang; Hai Guo; Da-Wei Huang; Lu Li; Hui-Yun Liu; Long Sui; Qian Wu; Jing-Jing Zhu; Lei Zhang; Cheng-Gang Niu (Chemical Engineering Journal, 2024)

Dihydrotanshinone I reduces H9c2 cell damage by regulating AKT and MAPK signaling pathways - Ya-chao Wang; Yi-da Shao; Chang-le Shao; Xiao-qi Guan; Ping-ping Lu; Ke Ning; Bao-nian Liu; Hai-dong Guo (In Vitro Cellular & Developmental Biology - Animal, 2024)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Probabilistic-based seismic fragility assessment of earthquake-induced site liquefaction - Jian-Yu Meng; Da-Gang Lu; Bao-Hua Shan (Soil Dynamics and Earthquake Engineering, 2023)

Targeted clearance of mitochondria by an autophagy-tethering compound (ATTEC) and its potential therapeutic effects - Shuixia Tan; Da Wang; Yuhua Fu; Huiwen Zheng; Yan Liu; Boxun Lu (Science Bulletin, 2023)

Oyster shell-derived CuFe2O4-Hap nanocomposite for healthy houses: Bacterial and formaldehyde elimination - Jinfeng Lu; Boji Zhou; Xiaoyan Zhang; Xiaoyan Zhao; Xiangmei Liu; Shuilin Wu; Da-Peng Yang (Chemical Engineering Journal, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Permafrost change and its engineering effects under climate change and airport construction scenarios in northeast China - Ming Guo; Yan Lu; Wenbing Yu; Lilin Xu; Da Hu; Lin Chen (Transportation Geotechnics, 2023)

Exploring risk-targeted ground motions and seismic design spectra for mainland China - Cong Wang; Da-Gang Lu (Soil Dynamics and Earthquake Engineering, 2023)

Recent advances in carbon dots-based nanoplatforms: Physicochemical properties and biomedical applications - Shiqiao Rui; Luming Song; Jiaru Lan; Da Wang; Shuaipeng Feng; Junya Lu; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2023)

Piezoelectric self-power supply driven by ferroelastic host–guest supramolecule with considerable electromechanical conversion capability - Meng-Meng Lun; Jia-Qi Luo; Zhi-Xu Zhang; Jie Li; Li-Yan Xie; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2023)

Molecular dynamics simulation on the dissolution and diffusion characteristics of FeCrAl alloy in liquid LBE - Lu Xie; Guang Da Wu; Qing Peng; Wen Rui Wang (Annals of Nuclear Energy, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Microbial communities and their correlation with flavor compound formation during the mechanized production of light-flavor Baijiu - Lu-Jun Luo; Liang Song; Ying Han; Pan Zhen; Da-Yong Han; Xin Zhao; Xin Zhou; Yu-Hua Wei; Hui-Xin Yu; Pei-Jie Han; Feng-Yan Bai (Food Research International, 2023)

Elastic Wavefield Decomposition for Reverse-Time Migration in 3D Transverse Isotropic Media - Jiahui Zuo; Fenglin Niu; Lele Zhang; Lu Liu; Houzhu Zhang; Ke Chen; Da Shuai; Jidong Yang; Yang Zhao (Pure and Applied Geophysics, 2023)

Identification of watermelon H3K4 and H3K27 genes and their expression profiles during watermelon fruit development - Yang Qiao; Yan-Ge Li; Tong-Lu Wei; Hai-Nan Liu; Mao-Song Pei; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Molecular Biology Reports, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Characterization of the vertical evolution of urban nocturnal boundary layer by UAV measurements: Insights into relations to cloud radiative effect - Lin Shen; Jiaoshi Zhang; Yin Cheng; Xiaofeng Lu; Haosheng Dai; Dexia Wu; Da-Ren Chen; Jianguo Liu; Huaqiao Gui (Environmental Research, 2023)

A novel approach to examining the optimal use of the cooling effect of water bodies in urban planning - Zehongyu Kang; Hua Liu; Yuxin Lu; Xinyu Yang; Xin Zhou; Jingjing An; Da Yan; Xing Jin; Xing Shi (Building and Environment, 2023)

Systemic lupus erythematosus with high disease activity identification based on machine learning - Da-Cheng Wang; Wang-Dong Xu; Zhen Qin; Lu Fu; You-Yu Lan; Xiao-Yan Liu; An-Fang Huang (Inflammation Research, 2023)

Correction to: Genome‑wide characterization of long terminal repeat retrotransposons provides insights into trait evolution of four cucurbit species - Hai‑Nan Liu; Mao‑Song Pei; Charles Ampomah‑Dwamena; Guang‑Qi He; Tong‑Lu Wei; Qiao‑Fang Shi; Yi‑He Yu; Da‑Long Guo (Functional & Integrative Genomics, 2023)

Genome-wide characterization of long terminal repeat retrotransposons provides insights into trait evolution of four cucurbit species - Hai-Nan Liu; Mao-Song Pei; Charles Ampomah-Dwamena; Guang-Qi He; Tong-Lu Wei; Qiao-Fang Shi; Yi-He Yu; Da-Long Guo (Functional & Integrative Genomics, 2023)

Constructing BiOBr/TiO2 heterostructure nanotubes for enhanced adsorption/photocatalytic performance - Sheng-Zhe Zhao; Yun Lu; Ran Lu; Yong-Da Hu; Raul D. Rodriguez; Jin-Ju Chen (Journal of Water Process Engineering, 2023)

Enterobacter sp. E1 increased arsenic uptake in Pteris vittata by promoting plant growth and dissolving Fe-bound arsenic - Aiting Li; Yingying Lu; Da Zhen; Ziheng Guo; Gejiao Wang; Kaixiang Shi; Shuijiao Liao (Chemosphere, 2023)

Petrogenesis of Sn-related granitoids and implications for the formation of the world-class Gejiu Sn district, South China: Insights from whole-rock and accessory mineral geochemistry - Xin Li; Yuan-chuan Zheng; Yang Shen; Chang-da Wu; Pei-yan Xu; Yan-shen Yang; Lu Wang; Zeng-qian Hou (Lithos, 2023)

A theoretical model on unfrozen water content in soils and verification - Wan Xusheng; Zhu Jishuai; Pei Wansheng; Zhou Fengxi; Lu Jianguo; Yan Zhongrui; Wa Da (Journal of Hydrology, 2023)

Revealing the influence of microbiota on the flavor of kombucha during natural fermentation process by metagenomic and GC-MS analysis - Lingyun Yao; Jing Zhang; Jun Lu; Da Chen; Shiqing Song; Huatian Wang; Min Sun; Tao Feng (Food Research International, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Unravelling the role of reactive oxygen species in ultrathin Z-scheme heterojunction with surface zinc vacancies for photocatalytic H2O2 generation and CTC degradation - Hui-Yun Liu; Cheng-Gang Niu; Da-Wei Huang; Chao Liang; Hai Guo; Ya-Ya Yang; Lu Li (Chemical Engineering Journal, 2023)

Runx2 overexpression promotes bone repair of osteonecrosis of the femoral head (ONFH) - Hai-Jia Xu; Xiang-Zhong Liu; Lu Yang; Yu Ning; Liang-Liang Xu; Da-Ming Sun; Wen Liao; Yi Yang; Zhang-Hua Li (Molecular Biology Reports, 2023)
Background Runt-related transcription factor-2 (Runx2) has been considered an inducer to improve bone repair ability of mesenchymal stem cells (MSCs). Methods and results Twenty-four rabbits were used to establish Osteonecrosis of the femoral head (ONFH) and randomly devided into four groups: Adenovirus Runx2 (Ad-Runx2) group, Runx2-siRNA group, MSCs group and Model group. At 1 week after model establishment, the Ad-Runx2 group was treated with 5 × 107 MSCs transfected through Ad-Runx2, the Runx2-siRNA group was treated with 5 × 107 MSCs transfected through Runx2-siRNA, the MSCs group was injected with 5 × 107 untreated MSCs, and the Model group was treated with saline. The injection was administered at 1 week and 3 weeks after model establishment. The expression of bone morphogenetic protein 2 (BMP-2), Runx2 and Osterix from the femoral head was detected at 3 and 6 weeks after MSCs being injected, and Masson Trichrome Staining, Gross Morphology, X-ray and CT images observation were used to evaluate the repair effect of ONFH. The data revealed that the expression of BMP-2, Runx2 and Osterix in the Runx2-siRNA group was reduced at 3 weeks compared with the MSCs group, and then the expression further reduced at 6 weeks, but was still higher than the Model group besides Osterix; The expression of these three genes in the Ad-Runx2 group was higher than in the MSCs group. Masson Trichrome Staining, Gross Morphology and X-ray and CT images observation revealed that necrotic femoral head of the MSCs group was more regular and smooth than the Runx2-siRNA group, which has a collapsed and irregular femoral head. In the Ad-Runx2 group, necrotic femoral head was basically completely repaired and covered by rich cartilage and bone tissue. Conclusions Overexpression of Runx2 can improve osteoblastic phenotype maintenance of MSCs and promote necrotic bone repair of ONFH.

Lupus nephritis or not? A simple and clinically friendly machine learning pipeline to help diagnosis of lupus nephritis - Da-Cheng Wang; Wang-Dong Xu; Shen-Nan Wang; Xiang Wang; Wei Leng; Lu Fu; Xiao-Yan Liu; Zhen Qin; An-Fang Huang (Inflammation Research, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

A simple and efficient protocol for transient transformation of sliced grape berries - Mao-Song Pei; Hai-Nan Liu; Charles Ampomah-Dwamena; Tong-Lu Wei; Yi-He Yu; Jia-Bing Jiao; Ying-Ying Lv; Feng Li; Hong-Chao Li; Xue-Jie Zhu; Da-Long Guo (Protoplasma, 2023)

Ultrapotassic enclaves in the Miocene adakitic granitoids, southern Tibet: Direct evidence for collision-related crust-mantle interaction and its implications - Chang-da Wu; Yuan-chuan Zheng; Bo Xu; Zeng-qian Hou; Peng Chai; Xin Li; Lin-yuan Zhang; Zi-xuan Wang; Lu Wang; Yang Shen (Lithos, 2023)

Visualization of biochar colloids transport and retention in two-dimensional porous media - Ying Zhao; Da Fan; Shaohua Cao; Wenxi Lu; Fan Yang (Journal of Hydrology, 2023)

Effects of activation and assisted reproduction techniques on the composition, structure, and properties of the sauger (Sander Canadensis) spermatozoa plasma membrane - Bryan Blawut; Barbara Wolfe; Chris Premanandan; Gustavo Schuenemann; Stuart A. Ludsin; Shan-Lu Liu; D.N. Rao Veeramachaneni; Marco A. Coutinho da Silva (Theriogenology, 2023)

Seasonal source identification and formation processes of marine particulate water soluble organic nitrogen over an offshore island in the East China Sea - Mengke Tian; Hao Li; Guochen Wang; Mengxin Fu; Xiaofei Qin; Da Lu; Chengfeng Liu; Yucheng Zhu; Xingzhang Luo; Congrui Deng; Sabur F. Abdullaev; Kan Huang (Science of The Total Environment, 2023)

Impacts of global urban expansion on natural habitats undermine the 2050 vision for biodiversity - Qiang Ren; Chunyang He; Qingxu Huang; Da Zhang; Peijun Shi; Wenlu Lu (Resources, Conservation and Recycling, 2023)

Folic acid delays postharvest quality deterioration of table grape by regulating cell wall metabolism-associated hub WRKY31 transcription factor - Mao-Song Pei; Hai-Nan Liu; Yi-He Yu; Tong-Lu Wei; Da-Long Guo (Postharvest Biology and Technology, 2023)

Appropriate oxygen vacancies and Mo-N bond synergistically modulate charge transfer dynamics of MoO3−x/S-CN for superior photocatalytic disinfection: Unveiling synergistic effects and disinfection mechanism - Ya-Ya Yang; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Hao-Peng Feng; Lu Li; Hui-Yun Liu; Qian-Qian Fan; Meng-Zhu Qin (Journal of Hazardous Materials, 2023)

Development of an automated solid phase extraction instrument for determination of lead in high-salt foods - Yabing Xiao; Yihan He; Chao Ji; Marti Z. Hua; Wei Liu; Shuang Yang; Da Chen; Wenjie Zheng; Xiaonan Lu (Food Chemistry, 2023)

Electron transfer enhancing the Mn(II)/Mn(III) cycle in MnO/CN towards catalytic ozonation of atrazine via a synergistic effect between MnO and CN - Da Wang; Yinning He; Yi Chen; Fan Yang; Zhiqiao He; Tao Zeng; Xiaohui Lu; Lizhang Wang; Shuang Song; Jun Ma (Water Research, 2023)

Synergistic nanowire-assisted electroporation and chlorination for inactivation of chlorine-resistant bacteria in drinking water systems via inducing cell pores for chlorine permeation - Ying-Wen Lu; Xiang-Xing Liang; Chen-Yang Wang; Da Chen; Hai Liu (Water Research, 2023)

Catalytic ozonation for imazapic degradation over kelp-derived biochar: Promotional role of N- and S-based active sites - Da Wang; Shiwen Dong; Siqi Fu; Yi Shen; Tao Zeng; Weiti Yu; Xiaohui Lu; Lizhang Wang; Shuang Song; Jun Ma (Science of The Total Environment, 2023)

Synergy between sulfur vacancy and Schottky junction into CoB/ZnIn2S4–S photocatalysts: Oriented charge flow and regulated carriers transfer dynamics to activate reactive oxygen species generation for efficient photocatalytic disinfection - Hui-Yun Liu; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Meng-Ke Li; Ya-Ya Yang; Ning Tang; Lu Li; Lei Zhang (Journal of Cleaner Production, 2023)

Creep characteristics of thermally-stressed Beishan granite under triaxial compression - Jian-Feng Liu; Xing Luo; Gan Feng; Lu-Lin Zhou; Xing-Guo Yang; Gong-Da Lu (International Journal of Rock Mechanics and Mining Sciences, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

DNAzymes-conjugated upconversion nanoamplicon for in-situ ultrasensitive detection and imaging of microRNA in vivo - Yi Zhang; Da Luo; Yin Zhang; Qi-Hai Zhang; Qing-Yuan Ji; Shi-Kang Zhou; Shan Huang; Li-li Li; Feng Lu; Wei-Feng Yao; Fang-Fang Cheng; Jun-Jie Zhu; et al. (Chemical Engineering Journal, 2023)

Selection of optimal seismic intensity measures using fuzzy-probabilistic seismic demand analysis and fuzzy multi-criteria decision approach - Ming-Yang Xu; Da-Gang Lu; Xiao-Hui Yu; Ming-Ming Jia (Soil Dynamics and Earthquake Engineering, 2023)

Toughing epoxy nanocomposites with graphene-encapsulated liquid metal framework - Da Li; E Peng; Fei Lu; Baolong Wang; Yibo Shen; Pengxiang Liu; Li Liu; Yudong Huang; Zhen Hu (Chemical Engineering Journal, 2023)

Catalytic ozonation of atrazine with stable boron-doped graphene nanoparticles derived from waste polyvinyl alcohol film: Performance and mechanism - Da Wang; Shiwen Dong; Hangkai Hu; Zhiqiao He; Feilong Dong; Juntao Tang; Xiaohui Lu; Lizhang Wang; Shuang Song; Jun Ma (Chemical Engineering Journal, 2023)

Structure and Function of Cationic and Ionizable Lipids for Nucleic Acid Delivery - Da Sun; Zheng-Rong Lu (Pharmaceutical Research, 2023)

Achiasmatic meiosis in the unisexual Amazon molly, Poecilia formosa - Dmitrij Dedukh; Irene da Cruz; Susanne Kneitz; Anatolie Marta; Jenny Ormanns; Tomáš Tichopád; Yuan Lu; Manfred Alsheimer; Karel Janko; Manfred Schartl (Chromosome Research, 2022)
Unisexual reproduction, which generates clonal offspring, is an alternative strategy to sexual breeding and occurs even in vertebrates. A wide range of non-sexual reproductive modes have been described, and one of the least understood questions is how such pathways emerged and how they mechanistically proceed. The Amazon molly, Poecilia formosa , needs sperm from males of related species to trigger the parthenogenetic development of diploid eggs. However, the mechanism, of how the unreduced female gametes are produced, remains unclear. Cytological analyses revealed that the chromosomes of primary oocytes initiate pachytene but do not proceed to bivalent formation and meiotic crossovers. Comparing ovary transcriptomes of P. formosa and its sexual parental species revealed expression levels of meiosis-specific genes deviating from P. mexicana but not from P. latipinna . Furthermore, several meiosis genes show biased expression towards one of the two alleles from the parental genomes. We infer from our data that in the Amazon molly diploid oocytes are generated by apomixis due to a failure in the synapsis of homologous chromosomes. The fact that this failure is not reflected in the differential expression of known meiosis genes suggests the underlying molecular mechanism may be dysregulation on the protein level or misexpression of a so far unknown meiosis gene, and/or hybrid dysgenesis because of compromised interaction of proteins from diverged genomes.

Germanium enrichment in sphalerite with acicular and euhedral textures: an example from the Zhulingou carbonate-hosted Zn(-Ge) deposit, South China - Kai Luo; Alexandre Cugerone; Mei-Fu Zhou; Jia-Xi Zhou; Guo-Tao Sun; Jing Xu; Kang-Jian He; Mao-Da Lu (Mineralium Deposita, 2022)

Long‐term drought aggravates instability of alpine grassland productivity to extreme climatic event - Yun L. He; Jin S. Wang; Da S. Tian; Quan Quan; Lin Jiang; Fang F. Ma; Lu Yang; Fang Y. Zhang; Qing P. Zhou; Shu L. Niu (Ecology, 2022)
The frequency and severity of extreme weather events are increasing and expected to increase more in the future, together with global change. However, how extreme events and global change factors interactively influence community structures and ecosystem processes is largely unknown. Here, we investigated the responses of the temporal stability and resilience of aboveground net primary productivity (ANPP) of an alpine meadow to an extreme flooding event under different treatments of experimental drought and clipping. We found that ecosystems that were exposed to drought treatments for 3 years significantly decreased the temporal stability of community productivity but increased resilience to flooding, whereas their resistance to or recovery from flooding did not change. Neither clipping nor its interaction with drought altered the responses of these community stability metrics to flooding. Drought treatments significantly decreased plant species richness and asynchrony and dominant species stability, leading to a decrease in temporal stability and an increase in resilience in response to the extreme flooding event. The study also revealed that the change in species asynchrony was the dominant impact pathway determining the responses of resilience and temporal stability to flooding. Our results highlight that alpine grassland that experiences a multiyear drought may aggravate the instability of community productivity to extreme climatic events by reducing species asynchrony.

Preliminary analysis of a landslide-dammed lake induced by two consecutive earthquakes on June 1, 2022, Sichuan Province, China - Nan Jiang; Cong-jiang Li; Hai-bo Li; Zhi-dong Zhou; Gong-da Lu; Jia-wen Zhou (Landslides, 2022)

Correction to: Protective effects of fowl‑origin cadmium‑tolerant lactobacillus against sub‑chronic cadmium‑induced toxicity in chickens - Da‑Wei Chen; Hui‑Jia Li; YinYin Liu; Li‑Na Ma; Jun‑Hua Pu; JunXian Lu; Xiu‑Jun Tang; Yu‑shi Gao (Environmental Science and Pollution Research, 2022)

Greenhouse gas emission benefits of adopting new energy vehicles in Suzhou City, China: A case study - Cui Da; Xinyu Gu; Chunchen Lu; Ruiqi Hua; Xinyue Chang; Yuanyuan Cheng; Feiyue Qian; Yiheng Wang (Environmental Science and Pollution Research, 2022)

Protective effects of fowl-origin cadmium-tolerant lactobacillus against sub-chronic cadmium-induced toxicity in chickens - Da-Wei Chen; Hui-Jia Li; YinYin Liu; Li-Na Ma; Jun-Hua Pu; JunXian Lu; Xiu-Jun Tang; Yu-shi Gao (Environmental Science and Pollution Research, 2022)

Correction to: Microvirga puerhi sp. nov., isolated from Puerh tea garden soil - Zhi-Da Zi; Wen Wen; Fu Ma; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2022)

Air pollution associated with cognitive decline by the mediating effects of sleep cycle disruption and changes in brain structure in adults - Chen-Chen Lo; Wen-Te Liu; Yueh-Hsun Lu; Dean Wu; Chih-Da Wu; Ting-Chieh Chen; Yu-Ting Fang; Yu-Chun Lo; You-Yin Chen; Lo Kang; Cheng-Yu Tsai; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Microvirga puerhi sp. nov., isolated from Puerh tea garden soil - Zhi-Da Zi; Wen Wen; Fu Ma; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2022)

3D Anisotropic P- and S-Mode Wavefields Separation in 3D Elastic Reverse-Time Migration - Jiahui Zuo; Fenglin Niu; Lu Liu; Shuai Da; Houzhu Zhang; Jidong Yang; Lele Zhang; Yang Zhao (Surveys in Geophysics, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Different Surface Appearances Caused by Unbalanced Mn2+ Accumulation in Gallstones Consisting of Cholesterol and CaCO3 Obtained from a Patient After Cholecystectomy - Da-Yong Lu; Jin Zhang; Qiao-Li Liu; Hong-Guang Wang; Meng Cui (Biological Trace Element Research, 2022)

Biomechanical Changes on the Typical Sites of Pressure Ulcers in the Process of Turning Over from Supine Position: Theoretical Analysis, Simulation, and Experiment - Peng Su; Qinglong Lun; Da Lu; Qiulong Wu; Tian Liu; Leiyu Zhang (Annals of Biomedical Engineering, 2022)

Polymer molecular morphology in alkali-surfactant-polymer (ASP) ternary composite system and its influence on rock pore structure - Xiaohan Nan; Bin Huang; Yihuan Wang; Da Guo; Lu Zhang; Wei Guo; Siqi Wang (Arabian Journal of Geosciences, 2022)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Multi-omics analysis reveals metabolism of okadaic acid in gut lumen of rat - Yang Liu; Yang Lu; Yu-Hu Jiao; Da-Wei Li; Hong-Ye Li; Wei-Dong Yang (Archives of Toxicology, 2022)

Identification and expression analysis of grape LRK10L-2 genes during grape fruit development - Jin-Ping Ma; Xue-Ren Yin; Tong-Lu Wei; Hai-Nan Liu; Mao-Song Pei; Sheng-Di Yang; Hui-Ying Jin; Guang-Qi He; Da-Long Guo (Plant Biotechnology Reports, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Two new nor-sesquiterpenoids from Fusarium tricinctum , an endophytic fungus isolated from Ligusticum chuanxiong - Yu-Mei Cao; Da-Le Guo; Meng-Ying Jin; Lu Tan; Tian-Long Yang; Fang Deng; Yu-Cheng Gu; Xiao-Hua Li; Zhi-Xing Cao; Yun Deng (Natural Product Research, 2021)

Conservation resource allocation, small population resiliency, and the fallacy of conservation triage - David A. Wiedenfeld; Allison C. Alberts; Ariadne Angulo; Elizabeth L. Bennett; Onnie Byers; Topiltzin Contreras‐MacBeath; Gláucia Drummond; Gustavo A. B. da Fonseca; Claude Gascon; Ian Harrison; Nicolas Heard; Axel Hochkirch; et al. (Conservation Biology, 2021)
Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss.

Purple non-sulfur bacteria technology: a promising and potential approach for wastewater treatment and bioresources recovery - Haifeng Lu; Guangming Zhang; Shichao He; Ruihan Zhao; Da Zhu (World Journal of Microbiology and Biotechnology, 2021)

Devosia sediminis sp. nov., isolated from subterranean sediment - Fu Ma; Zhi-Da Zi; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2021)

A comprehensive assessment and analysis of Antarctic satellite grounding line products from 1992 to 2009 - Rongxing Li; Da Lv; Huan Xie; Yixiang Tian; Yang Xu; Saisai Lu; Xiaohua Tong; Hexia Weng (Science China Earth Sciences, 2021)

Efficacy of Targeted ECO/miR-200c Nanoparticles for Modulating Tumor Microenvironment and Treating Triple Negative Breast Cancer as Non-invasively Monitored by MR Molecular Imaging - Andrew L. Schilb; Nadia R. Ayat; Amita M. Vaidya; Laura M. Hertz; Ryan C. Hall; Josef H. Scheidt; Da Sun; Zhanhu Sun; Ramamurthy Gopalakrishnan; Zheng-Rong Lu (Pharmaceutical Research, 2021)

Decreased calcium concentration interferes with life history defense strategies of Ceriodaphnia cornuta in response to fish kairomone - Jing Huang; Xiaoqing Xu; Da Li; Yunfei Sun; Lei Gu; Lu Zhang; Kai Lyu; Zhou Yang (Limnology and Oceanography, 2021)
Declining calcium in freshwater lakes has become a serious threat to aquatic organisms, which may affect the anti‐fish defense of cladocerans with high calcium demand. To evaluate the effects of low calcium on life history strategies of cladocerans for defending against fish predation, we exposed Ceriodaphnia cornuta to eight concentrations of calcium ranging from 0.5 to 50.0 mg L −1 in the absence and presence of fish kairomone, and observed the changes in body surface, recorded the key life‐history traits, and calculated the degree of its induced defense response. Results showed that, on average, low calcium (0.5, 1.0, 1.5 mg L −1 ) significantly reduced survival, maternal body size at maturation, and total offspring per female by 66.7%, 8.0%, and 48.8%, respectively, compared with those exposed to normal calcium level (10.0 mg L −1 ). At the normal calcium level, fish kairomone shortened the time to maturation, reduced maternal body size at maturation, and increased total offspring by 15.7%, 11.0%, and 29.6%, respectively, compared with those not exposed to fish kairomone. In the presence of fish kairomone, the reproduction of C. cornuta was affected by a narrower range of calcium concentrations. Calcium concentrations and fish kairomone showed a significant interaction on maternal body size at maturation, total offspring, and body size of neonates, i.e., low calcium impaired the life history defenses involved in maternal development, but enhanced the defense traits involved in reproductive performance, which indicated the diversified interference effects of decreased calcium on the life history defense strategies of C. cornuta against fish predators.

Influence of size gradation on particle separation and the motion behaviors of debris avalanches - Yu-xiang Hu; Hai-bo Li; Gong-da Lu; Gang Fan; Jia-wen Zhou (Landslides, 2021)

Disinfection efficiency of hospital infectious disease wards with chlorine dioxide and hypochlorous acid - Ming-Chun Lu; Po-Lin Chen; Da-Ji Huang; Chih-Kuo Liang; Ching-Shan Hsu; Wei-Ting Liu (Aerobiologia, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

A new cyclic peptide from the fibrous root of Pseudostellaria heterophylla - Xiao-fei Zhao; Qian Zhang; Han-tao Zhao; Yan-da Zhang; Han-ru Liu; Lu-jiang Yuan; Qian-feng Chen (Natural Product Research, 2020)

Fucoxanthin Mitigates Subarachnoid Hemorrhage-Induced Oxidative Damage via Sirtuin 1-Dependent Pathway - Xiang-Sheng Zhang; Yue Lu; Tao Tao; Han Wang; Guang-Jie Liu; Xun-Zhi Liu; Cang Liu; Da-Yong Xia; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2020)

Safety threshold of blasting vibration velocity in foundation excavation of Baihetan super-high arch dam - Wenjun Xia; Wenbo Lu; Gaohui Wang; Peng Yan; Da Liu; Zhendong Leng (Bulletin of Engineering Geology and the Environment, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Detailed Analysis of Lipids in Edible Viscera and Muscles of Cooked Crabs Portunus trituberculatus and Portunus pelagicus - Ting Lu; Yan Shen; Guo-Xin Cui; Fa-Wen Yin; Zhuo-Liang Yu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2020)

Experimental study on the formation of landslide dams by fragmentary materials from successive rock slides - Hai-mei Liao; Xing-guo Yang; Gong-da Lu; Jian Tao; Jia-wen Zhou (Bulletin of Engineering Geology and the Environment, 2020)

Development of an indirect ELISA for detecting porcine deltacoronavirus IgA antibodies - Manman Lu; Qiuge Liu; Xiaobo Wang; Jialin Zhang; Xin Zhang; Da Shi; Jianbo Liu; Hongyan Shi; Jianfei Chen; Li Feng (Archives of Virology, 2020)

Association between lifestyle, dietary, reproductive, and anthropometric factors and circulating 27-hydroxycholesterol in EPIC-Heidelberg - Charlotte Le Cornet; Theron S. Johnson; Da-Lin Lu; Rudolf Kaaks; Renée Turzanski Fortner (Cancer Causes & Control, 2020)

Methodology for production logging in oil-in-water flows under low flow rate and high water-cut conditions - Da-Yang Wang; Ning-De Jin; Lu-Sheng Zhai; Ying-Yu Ren; Yuan-Sheng He (Applied Geophysics, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

CaMYC, A Novel Transcription Factor, Regulates Anthocyanin Biosynthesis in Color-leaved Pepper (Capsicum annuum L.) - Bo-Ya Lu; Guo-Xin Cheng; Zhen Zhang; Jian-Tian Sun; Muhammad Ali; Qing-Li Jia; De-Xu Luo; Zhen-Hui Gong; Da-Wei Li (Journal of Plant Growth Regulation, 2019)

Time Effects on Resting EEG in Children With/Without AD/HD - Da-Wei Zhang; Stuart J. Johnstone; Hui Li; Robert J. Barry; Adam R. Clarke; Qihua Zhao; Yan Song; Lu Liu; Qiujin Qian; Yufeng Wang; Li Sun (Brain Topography, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

An ensemble-based likelihood ratio approach for family-based genomic risk prediction - Hui An; Chang-shuai Wei; Oliver Wang; Da-hui Wang; Liang-wen Xu; Qing Lu; Cheng-yin Ye (Journal of Zhejiang University-SCIENCE B, 2018)

Ambient air pollution of particles and gas pollutants, and the predicted health risks from long-term exposure to PM2.5 in Zhejiang province, China - Yuanchen Chen; Lu Zang; Wei Du; Da Xu; Guofeng Shen; Quan Zhang; Qiaoli Zou; Jinyuan Chen; Meirong Zhao; Defei Yao (Environmental Science and Pollution Research, 2018)

Methyl jasmonate and salicylic acid elicitation increase content and yield of chlorogenic acid and its derivatives in Gardenia jasminoides cell suspension cultures - Ze-Bo Liu; Ji-Guang Chen; Zhong-Ping Yin; Xin-Chen Shangguan; Da-Yong Peng; Tao Lu; Ping Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Improvement of indoor air quality in pet shop using gaseous chlorine dioxide - Ming-Chun Lu; Da-Ji Huang; Ching-Shan Hsu; Chih-Kuo Liang; Geng-Min Chen (Environmental Monitoring and Assessment, 2018)

Whole sequence analysis indicates a recent southern origin of Mongolian Y-chromosome C2c1a1a1-M407 - Yun-Zhi Huang; Lan-Hai Wei; Shi Yan; Shao-Qing Wen; Chuan-Chao Wang; Ya-Jun Yang; Ling-Xiang Wang; Yan Lu; Chao Zhang; Shu-Hua Xu; Da-Li Yao; Li Jin; et al. (Molecular Genetics and Genomics, 2018)

Sevoflurane Affects Oxidative Stress and Alters Apoptosis Status in Children and Cultured Neural Stem Cells - Xue Zhou; Dihan Lu; Wen-da Li; Xiao-hui Chen; Xiao-yu Yang; Xi Chen; Zhi-bin Zhou; Jiang-Hong Ye; Xia Feng (Neurotoxicity Research, 2018)

HpaP, a novel regulatory protein with ATPase and phosphatase activity, contributes to full virulence in Xanthomonas campestris pv. campestris - Ping Cui; Rui‐Fang Li; Da‐Pei Zhang; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2018)
Summary The ability of the bacterial phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on the type III secretion system (T3SS). Proteins of the Xcc T3SS are encoded by hrp (hypersensitive response and pathogenicity) genes and whose expression is mainly controlled by the regulators HrpG and HrpX. Here, we describe the identification and characterization of a previously unknown regulatory protein ( named HpaP), which plays important role in hrp gene expression and virulence in Xcc . Clean deletion of hpaP demonstrated reduced virulence and HR (hypersensitive response) induction of Xcc and alterations in cell motility and stress tolerance. Global transcriptome analyses revealed that most hrp genes were down regulated in the hpaP mutant, suggesting HpaP positively regulates hrp genes. GUS activity assays implied that HpaP regulates the expression of hrp genes via controlling the expression of hrpX . Biochemical analyses revealed that HpaP protein had both ATPase and phosphatase activity. While further site‐directed mutagenesis of conserved residues in the PTP loop (a protein tyrosine phosphatase signature) of HpaP resulted in the loss of both phosphatase activity and regulatory activity in virulence and HR. Taken together, the findings identify a new regulatory protein that controls hrp gene expression and virulence in Xcc .

Detection and complete genome characteristics of Posavirus 1 from pigs in China - Jianfei Chen; Manman Lu; Tianxin Ma; Liyan Cao; Xiangdong Zhu; Xin Zhang; Da Shi; Hongyan Shi; Jianbo Liu; Li Feng (Virus Genes, 2018)

Fuzzy probabilistic seismic hazard analysis with applications to Kunming city, China - Jelena M. Andrić; Da-Gang Lu (Natural Hazards, 2017)

Characteristics of ambient ozone (O3) pollution and health risks in Zhejiang Province - Yuanchen Chen; Lu Zang; Jinyuan Chen; Da Xu; Defei Yao; Meirong Zhao (Environmental Science and Pollution Research, 2017)

Cryopreservation of grapevine (Vitis spp.)—a review - Wen-Lu Bi; Chen Pan; Xin-Yi Hao; Zhen-Hua Cui; Mafatlal M. Kher; Zvjezdana Marković; Qiao-Chun Wang; Jaime A. Teixeira da Silva (In Vitro Cellular & Developmental Biology - Plant, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Quality analysis, classification, and authentication of liquid foods by near-infrared spectroscopy: A review of recent research developments - Lu Wang; Da-Wen Sun; Hongbin Pu; Jun-Hu Cheng (Critical Reviews in Food Science and Nutrition, 2017)

A three-dimensional rigorous method for stability analysis and its application - Kun Lin Lu; Da Yong Zhu (Bulletin of Engineering Geology and the Environment, 2016)

Comparing Four Dimension Reduction Algorithms to Classify Algae Concentration Levels in Water Samples Using Hyperspectral Imaging - Hongbin Pu; Lu Wang; Da-Wen Sun; Jun-Hu Cheng (Water, Air, & Soil Pollution, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Overexpression of the MYB transcription factor MYB28 or MYB99 confers hypersensitivity to abscisic acid in arabidopsis - Yong-Tao Yu; Zhen Wu; Kai Lu; Chao Bi; Shan Liang; Xiao-Fang Wang; Da-Peng Zhang (Journal of Plant Biology, 2016)

Impact of particulate and dissolved material on light absorption properties in a High-Altitude Lake in Tibet, China - Ciren Nima; Børge Hamre; Øyvind Frette; Svein Rune Erga; Yi-Chun Chen; Lu Zhao; Kai Sørensen; Marit Norli; Da-Ren Lu; Qian-Guo Xing; Yao-Ming Ma; Norsang Gelsor; et al. (Hydrobiologia, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Overexpression of the MYB37 transcription factor enhances abscisic acid sensitivity, and improves both drought tolerance and seed productivity in Arabidopsis thaliana - Yong-Tao Yu; Zhen Wu; Kai Lu; Chao Bi; Shan Liang; Xiao-Fang Wang; Da-Peng Zhang (Plant Molecular Biology, 2016)

Potential natural exposure of endangered red-crowned crane (Grus japonensis) to mycotoxins aflatoxin B1, deoxynivalenol, zearalenone, T-2 toxin, and ochratoxin A - Da-wei Liu; Hong-yi Liu; Hai-bin Zhang; Ming-chang Cao; Yong Sun; Wen-da Wu; Chang-hu Lu (Journal of Zhejiang University-SCIENCE B, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Prediction of Plant Vulnerability to Salinity Increase in a Coastal Ecosystem by Stable Isotope Composition (δ18O) of Plant Stem Water: A Model Study - Lu Zhai; Jiang Jiang; Donald DeAngelis; Leonel da Silveira Lobo Sternberg (Ecosystems, 2016)

Estrogen Receptor Alpha (ERα)-Associated Fibroblasts Promote Cell Growth in Prostate Cancer - Jun Da; Mujun Lu; Zhong Wang (Cell Biochemistry and Biophysics, 2015)

Residue behavior and risk assessment of mixed formulation of imidacloprid and chlorfenapyr in chieh-qua under field conditions - Jian Xiang Huang; Cong Yun Liu; Da Hai Lu; Jia Jia Chen; Yi Cai Deng; Fu Hua Wang (Environmental Monitoring and Assessment, 2015)

Crucial roles of the pentatricopeptide repeat protein SOAR1 in Arabidopsis response to drought, salt and cold stresses - Shang-Chuan Jiang; Chao Mei; Shan Liang; Yong-Tao Yu; Kai Lu; Zhen Wu; Xiao-Fang Wang; Da-Peng Zhang (Plant Molecular Biology, 2015)

Spectral Characteristics of Tropical Anvils Obtained by Combining TRMM Precipitation Radar with Visible and Infrared Scanner Data - Yuan-Jian Yang; Da-Ren Lu; Yun-Fei Fu; Feng-Jiao Chen; Yu Wang (Pure and Applied Geophysics, 2015)

Disinfection of indoor air microorganisms in stack room of university library using gaseous chlorine dioxide - Ching-Shan Hsu; Ming-Chun Lu; Da-Ji Huang (Environmental Monitoring and Assessment, 2015)

N-3 polyunsaturated fatty acids intake and risk of colorectal cancer: meta-analysis of prospective studies - Guo-Chong Chen; Li-Qiang Qin; Da-Bing Lu; Tie-Mei Han; Yan Zheng; Guo-Zhang Xu; Xiao-Huai Wang (Cancer Causes & Control, 2015)

Simvastatin Pretreatment Protects Cerebrum from Neuronal Injury by Decreasing the Expressions of Phosphor-CaMK II and AQP4 in Ischemic Stroke Rats - Min-xia Zhu; Chao Lu; Chun-mei Xia; Zhong-wei Qiao; Da-nian Zhu (Journal of Molecular Neuroscience, 2014)

Combined impacts of antecedent earthquakes and droughts on disastrous debris flows - Ning-sheng Chen; Yang Lu; Hai-bo Zhou; Ming-feng Deng; Da-wei Han (Journal of Mountain Science, 2014)

Effects of heat softening on initiation of landslides - Chuan-xiang Xiong; Xiao-bing Lu; Wei-da Huang; Cheng-hua Wang (Journal of Mountain Science, 2014)

Effect of pH on the physicochemical and heat-induced gel properties of scallop Patinopecten yessoensis actomyosin - Xiu-Ping Dong; Lu-Lu Ma; Jie Zheng; Ji-Tao Wang; Qiong Wu; Shuang Song; Da-Yong Zhou (Fisheries Science, 2014)

The “valley economy” model of regional development: A case study of mountain areas in Beijing, northern China - Chun-la Liu; Ming-xing Chen; Zhi-peng Tang; Wei-dong Liu; Da-dao Lu; Yi-feng Zhang (Journal of Mountain Science, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Porous-grain-upper-boundary model and its application to Tarim Basin carbonates - Yu-Qian Guo; Hong-Da Ma; Kai-Bo Shi; Hong Cao; Lu-Zhong Huang; Feng-Chang Yao; Tian-Yue Hu (Applied Geophysics, 2013)

Cochaperonin CPN20 negatively regulates abscisic acid signaling in Arabidopsis - Xiao-Feng Zhang; Tao Jiang; Zhen Wu; Shu-Yuan Du; Yong-Tao Yu; Shang-Chuan Jiang; Kai Lu; Xiu-Jing Feng; Xiao-Fang Wang; Da-Peng Zhang (Plant Molecular Biology, 2013)

A new turtle from the Xiagou Formation (Early Cretaceous) of Changma Basin, Gansu Province, P. R. China - Donald B. Brinkman; Chong-Xi Yuan; Qiang Ji; Da-Qing Li; Hai-Lu You (Palaeobiodiversity and Palaeoenvironments, 2013)

Noise filtering of full-gravity gradient tensor data - Yuan Yuan; Da-Nian Huang; Qing-Lu Yu; Mei-Xia Geng (Applied Geophysics, 2013)

Retinoic Acid and Human Olfactory Ensheathing Cells Cooperate to Promote Neural Induction From Human Bone Marrow Stromal Stem Cells - Song-Tao Xie; Fan Lu; Xi-Jing Zhang; Qi Shen; Zuping He; Wei-Qiang Gao; Da-Hai Hu; Hao Yang (NeuroMolecular Medicine, 2013)

Auto- and Cross-repression of Three Arabidopsis WRKY Transcription Factors WRKY18, WRKY40, and WRKY60 Negatively Involved in ABA Signaling - Lu Yan; Zhi-Qiang Liu; Yan-Hong Xu; Kai Lu; Xiao-Fang Wang; Da-Peng Zhang (Journal of Plant Growth Regulation, 2013)

A gain-of-function mutation in IAA8 alters Arabidopsis floral organ development by change of jasmonic acid level - Jing Wang; Da-Wei Yan; Ting-Ting Yuan; Xiang Gao; Ying-Tang Lu (Plant Molecular Biology, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Roles of the different components of magnesium chelatase in abscisic acid signal transduction - Shu-Yuan Du; Xiao-Feng Zhang; Zekuan Lu; Qi Xin; Zhen Wu; Tao Jiang; Yan Lu; Xiao-Fang Wang; Da-Peng Zhang (Plant Molecular Biology, 2012)

An Event-Related Potential Study of Maternal Love in Mothers - Jiamei Lu; Da Li; Jingwei Xu (Brain Topography, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Application of chlorine dioxide for disinfection of student health centers - Ching-Shan Hsu; Ming-Chun Lu; Da-Ji Huang (Environmental Monitoring and Assessment, 2012)

The cyclophosphamide metabolite, acrolein, induces cytoskeletal changes and oxidative stress in Sertoli cells - Feng Liu; Xu-Liang Li; Tao Lin; Da-Wei He; Guang-Hui Wei; Jun-Hong Liu; Lu-Sheng Li (Molecular Biology Reports, 2012)

Mesozoic collision-related magmatism and crust–mantle interaction along the Anhui segment of the Yangtze River Valley, east-central China - Da-Peng Li; Yang-Song Du; Ya-Fei Wang; Xin Lu; Yi Cao (International Geology Review, 2011)

In Vitro Evaluation of Phospholipase, Proteinase, and Esterase Activities of Candida parapsilosis and Candida metapsilosis - Yi Ping Ge; Gui Xia Lu; Yong Nian Shen; Wei Da Liu (Mycopathologia, 2011)

Evaluation of Left Ventricular Twist in Acute Myocardial Infarction Patients Using Speckle Tracking Imaging - Da-lin Jia; Chun-yan Ma; Shuang Liu; Lu-fan Sun (Cell Biochemistry and Biophysics, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

Expression of recombinant proteins in plants by using baculovirus vectors - Eun-Yi Oh; Young Kwan Kim; Da-Young Park; Zhe Lu; Young Kug Choo; Yeon Soo Han; Jeong Mee Park; Kisung Ko (Horticulture, Environment, and Biotechnology, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

Can the soil seed bank contribute to revegetation of the drawdown zone in the Three Gorges Reservoir Region? - Zhi-Jun Lu; Lian-Fa Li; Ming-Xi Jiang; Han-Dong Huang; Da-Chuan Bao (Plant Ecology, 2010)

UNC-64 and RIC-4, the plasma membrane-associated SNAREs syntaxin and SNAP-25, regulate fat storage in nematode Caenorhabditis elegans - Qiu-Li Wu; Qi Rui; Ke-Wen He; Lu-Lu Shen; Da-Yong Wang (Neuroscience Bulletin, 2010)

Genes required for the functions of olfactory AWA neuron regulate the longevity of Caenorhabditis elegans in an insulin/IGF signaling-dependent fashion - Lu-Lu Shen; Min Du; Xing-Feng Lin; Ting Cai; Da-Yong Wang (Neuroscience Bulletin, 2010)

Mesoscale barotropic instability of vortex Rossby waves in tropical cyclones - Wei Zhong; Han-Cheng Lu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2010)

Regulation of aging by unc-13 and sbt-1 in Caenorhabditis elegans is temperature-dependent - Ke-Wen He; Lu-Lu Shen; Wen-Wen Zhou; Da-Yong Wang (Neuroscience Bulletin, 2009)

Research progress in transient receptor potential vanilloid 1 of sensory nervous system - Da-Lu Liu; Wen-Ting Wang; Jun-Ling Xing; San-Jue Hu (Neuroscience Bulletin, 2009)

Superoxide dismutase and cytokines in chronic patients with schizophrenia: association with psychopathology and response to antipsychotics - Xiang Yang Zhang; Dong Feng Zhou; Ling Yan Qi; Song Chen; Lian Yuan Cao; Da Chun Chen; Mei Hong Xiu; Fan Wang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2009)

Parasite genetic differentiation by habitat type and host species: molecular epidemiology of Schistosoma japonicum in hilly and marshland areas of Anhui Province, China - JAMES W. RUDGE; DA‐BING LU; GUO‐REN FANG; TIAN‐PING WANG; MARÍA‐GLORIA BASÁÑEZ; JOANNE P. WEBSTER (Molecular Ecology, 2009)
Schistosoma japonicum , a parasite of significant public health importance in parts of China and Southeast Asia, is a true generalist pathogen with over 40 species of mammals suspected as definitive host reservoirs. In order to characterize levels of parasite gene flow across host species and identify the most important zoonotic reservoirs, S. japonicum larvae (miracidia) were sampled from a range of definitive host species in two contrasting habitat types within Anhui Province, China: a low‐lying marshland region, and a hilly region, where animal reservoir populations may be predicted to differ substantially. Miracidia samples were genotyped using seven multiplexed microsatellite markers. Hierarchical F ‐statistics and clustering analyses revealed substantial geographical structuring of S. japonicum populations within Anhui, with strong parasite genetic differentiation between habitat types. Within most villages, there was very little or no parasite genetic differentiation among host species, suggesting frequent S. japonicum gene flow, and thus also transmission, across species. Moreover, the data provide novel molecular evidence that rodents and dogs are potentially very important infection reservoirs in hilly regions, in contrast to bovines in the marshland regions. The parasite genetic differentiation between habitat types might therefore be associated with contrasting host reservoirs. The high levels of parasite gene flow observed across host species in sympatric areas have important implications for S. japonicum control, particularly in hilly regions where control of infection among wild rodent populations could be challenging.

Lower serum cytokine levels in smokers than nonsmokers with chronic schizophrenia on long-term treatment with antipsychotics - Xiang Yang Zhang; Lian Yuan Cao; Cai Song; Gui Ying Wu; Da Chun Chen; Ling Yan Qi; Fan Wang; Mei Hong Xiu; Song Chen; Yingyang Zhang; Lin Lu; Therese A. Kosten; et al. (Psychopharmacology, 2008)

Infection of green fluorescence protein-tagged Fusarium graminearum on wheat and barley spikes - Xu Zhang; Theo Lee; Marie Dufresne; Tai-guo Liu; Wei-zhong Lu; Da-zhao Yu; Hong-xiang Ma (Cereal Research Communications, 2008)

Glutathione S-transferases M1 and T1 polymorphisms and arsenic content in hair and urine in two ethnic clans exposed to indoor combustion of high arsenic coal in Southwest Guizhou, China - Guo-fang Lin; Hui Du; Ji-gang Chen; Hong-chao Lu; Jin-xiang Kai; Yun-shu Zhou; Wei-chao Guo; Xin-jiang Zhang; Da-ru Lu; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2007)

Determination of Nitrobenzene in Wastewater Using a Hanging Mercury Drop Electrode - Shu -Xuan Liang; Huan -Kun Zhang; Da Lu (Environmental Monitoring and Assessment, 2007)

Assignment of CCR7 gene to chicken chromosome 27 by radiation hybrid panel mapping - Yong Tian; Li-zhi Lu; Yan Fu; Zheng-rong Tao; Jun-da Shen; De-qian Wang; Ai-ping Yuan; Zhao-zheng Yin (Journal of Zhejiang University-SCIENCE B, 2007)

Involvement of genes required for synaptic function in aging control in C. elegans - Lu-Lu Shen; Yang Wang; Da-Yong Wang (Neuroscience Bulletin, 2007)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Application of near-infrared spectroscopy to predict sweetpotato starch thermal properties and noodle quality - Guo-quan Lu; Hua-hong Huang; Da-peng Zhang (Journal of Zhejiang University-SCIENCE B, 2006)

PCR-RFLP analysis ofcytochrome b gene does not supportCoilia ectenes taihuensis being a subspecies ofCoilia ectenes - Qi-Qun Cheng; Da-Ru Lu (Journal of Genetics, 2005)

pp5644 Interacts with phosphatidylinositol-4-phosphate adaptor protein-1 associated protein-1 - Xiao-Xia Ye; Hong Lu; Yao Yu; Ning Ding; Nai-Ling Zhang; Ke-Ke Huo; Da-Fang Wan; Yu-Yang Li; Jian-Ren Gu (Molecular and Cellular Biochemistry, 2005)

Identification and genetic relationships of kenaf (Hibiscus cannabinus L.) germplasm revealed by AFLP analysis - Zhou Cheng; Bao-Rong Lu; Kazuhiko Sameshima; Da-Xu Fu; Jia-Kuan Chen (Genetic Resources and Crop Evolution, 2004)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)